Noninvasive Determination of CMV Serostatus From Dried Buccal Swab Samples: Assay Development, Validation, and Application to 1.2 Million Samples. (13th February 2020) - Behrens, Geoffrey A; Brehm, Michael; Groß, Rita; Heider, Jana; Sauter, Jürgen; Baier, Daniel M; Wehde, Tatjana; Castriciano, Santina; Schmidt, Alexander H; Lange, Vinzenz
Abstract: Background: Buccal swab sampling constitutes an attractive noninvasive alternative to blood drawings for antibody serostatus assays. Here we describe a method to determine the cytomegalovirus immunoglobulin G (CMV IgG) serostatus from dried buccal swab samples. Methods: Upon solubilization, CMV IgG is determined by an ELISA assay specifically adapted to cope with low IgG concentrations. The derived CMV titer is normalized against the total protein concentration to adjust for incorrectly or less efficiently sampled buccal swabs. Assay parameters were optimized on a set of 713 samples. Results: Validation with 1784 samples revealed distinct results for > 80% of samples with 98.6% specificity and 99.1% sensitivity. Based on the analysis of 1.2 million samples we derived age- and sex-stratified CMV prevalence statistics for Germany, Poland, United Kingdom, and Chile. To confirm accuracy of the assay in routine operation, the CMV status of 6518 donors was reassessed by independent laboratories based on conventional blood samples revealing 96.9% specificity and 97.4% sensitivity. Conclusions: The assay accurately delivers the CMV IgG serostatus from dried buccal swab samples for > 80% of the participants. Thereby it provides a noninvasive alternative to plasma-based CMV monitoring for nondiagnostic purposes such as hematopoietic stem cell transplantation donor screening or population studies. Abstract : We developed an assay to determine the CMV IgG status based on dried buccal swab samples. Assay validation on a set of 1784 samples revealed 99% sensitivity and specificity. We describe CMV prevalence statistics for Germany, Poland, United Kingdom, and Chile.